2022
DOI: 10.1186/s12967-022-03745-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the frequency and the impact of pharmacogenetic alleles in an ancestrally diverse Biobank population

Abstract: Background Pharmacogenomics (PGx) aims to utilize a patient’s genetic data to enable safer and more effective prescribing of medications. The Clinical Pharmacogenetics Implementation Consortium (CPIC) provides guidelines with strong evidence for 24 genes that affect 72 medications. Despite strong evidence linking PGx alleles to drug response, there is a large gap in the implementation and return of actionable pharmacogenetic findings to patients in standard clinical practice. In this study, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In our clinic, all patients who received genetic testing had at least one actionable pharmacogenetic variant. This is similar to previously reported findings from the Mayo Clinic and the Penn Medicine Biobank, which both found that approximately 99% of participants had at least one actionable variant 12,31 . However, we found that a higher percentage of our patients had three or more actionable variants compared to what has been previously reported (74% vs. 58%) 31 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our clinic, all patients who received genetic testing had at least one actionable pharmacogenetic variant. This is similar to previously reported findings from the Mayo Clinic and the Penn Medicine Biobank, which both found that approximately 99% of participants had at least one actionable variant 12,31 . However, we found that a higher percentage of our patients had three or more actionable variants compared to what has been previously reported (74% vs. 58%) 31 .…”
Section: Discussionsupporting
confidence: 91%
“…10 Several real-world studies have reported that 20%-50% of patients are taking medications impacted by PGx variants. 9,11,12 Translation of PGx into the clinic has been facilitated by evidencebased guidelines published by the Clinical Pharmacogenetics Implementation Consortium (CPIC) and FDA-approved package labeling that provide genotype-guided medication recommendations, however PGx testing has not been widely adopted across clinical settings. 13 The University of Pennsylvania Health System (Penn Medicine) began PGx testing within a research setting for specific use cases such as cytochrome P450 2C19 (CYP2C19) testing for percutaneous coronary intervention 14 and dihydropyrimidine dehydrogenase (DPYD) variant testing for gastrointestinal cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] This is especially important in pharmacogenomics where there is a high proportion of actionable results and broad application beyond specialty clinics. [7,8]…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, multiple studies have demonstrated ancestry-specific patterns in these pharmacogenes [ 13 , 14 , 15 ], therefore, understanding the prevalence of these variants in multiple populations would help to target efforts in the implementation of pharmacogenetic testing with the greatest possible impact. In this context, the origin of the Chilean population is intricately intertwined with the Mapuche and Huilliche Amerindian communities, which has greatly enriched the nation’s cultural heritage.…”
Section: Introductionmentioning
confidence: 99%